Sexual choreographies of the classroom: movement in sexuality education. Issue 3 (4th May 2018) - Allen, Louisa
ABSTRACT: This paper is interested in thinking more about sexuality education at school. As such, it is concerned with a mundane and unacknowledged feature of the sexuality classroom – the mapping of movement. While human movement is a familiar focus of educational research, the movement of things is not. With reference to Barad's concept of intra-activity, the paper maps human-non-human movements and characterises these as a sexual choreography of schooling. Instead of asking what does movement mean or reveal about sexuality education, I attend to the event movement inaugurates. Predominantly theoretical, the paper weaves together ideas from conventionally disparate disciplinary fields. These include Edensor's concept of rhythm from geography, Eggermont's notion of the choreography of schooling from education, and Barad's spacetimemattering from quantum physics. This theorisation enables a recognition of movement as a force in human-non-human classroom intra-actions implicated in the becoming of sexuality education as event.